ANALISIS PENGARUH TINGKAT SOSIAL TERHADAP KUALITAS CALON GURU MELALUI INTEGRASI ASPEK KOGNITIF TAKSONOMI BLOOM DAN SOLO DALAM IMPLEMENTASI KURIKULUM 2013 - Meidasari, Venny Eka; Mawardi, Dalmeri; Suseno, Imam (Prosiding Pendidikan Teknik Boga Busana, 2020)
This paper focuses on integrating Bloom taxonomy and SOLO taxonomy as a valuable tool to assess the correlation between social stratification and cognitive level of Faculty of Education and Teacher Training (FKIP) students in private universities in Jakarta. Both taxonomies are often used individually as a framework for classifying statements of what we expect or intend students to learn as a result of instruction. In this paper, the writers integrate both of them as an innovation of learning assessment. Assessment is defined as the process of obtaining information that is used to make educational decisions about student, to give feedback to the student about his or her progress, strengths and weaknesses, to judge instructional effectiveness and curricular adequacy, and to inform policy, especially relating to the new policy of curriculum 2013. Various assessment techniques include, but are not limited to, formal and informal observations, qualitative and quantitative analysis of student performance and products, paper-and-pencil tests, oral questioning, and analysis of student records. The assessment competencies included are the knowledge and skills critical to a teacher or a teacher-to-be as the role of educator. Finally, this paper also suggests a new focus for research that will encompass a learning assessment method using the new approach of Bloom taxonomy and SOLO taxonomy integration that later can be integrated in any level of education curriculum included vocational school curriculum 2013. Keywords: Bloom taxonomy, SOLO taxonomy, social stratification, innovation, curriculum 2013.